Relative contributions of parental intention and provider recommendation style to HPV and meningococcal vaccine receipt - Terresa J. Eun; Amresh Hanchate; Anny T. Fenton; Jack A. Clark; Marisa N. Aurora; Mari-Lynn Drainoni; Rebecca B. Perkins (Taylor & Francis Group, 2019)
We described the relative contributions of parental intention and provider recommendation style to HPV and meningococcal vaccine receipt. Parent-child dyads that were eligible for both meningococcal and HPV vaccines participated in pre-visit surveys and consented to audio recording of their clinical interactions with healthcare providers related to vaccination. Surveys were analyzed for parent and child demographics and parental intention to vaccinate children with HPV and/or meningococcal vaccines. Audio recordings were analyzed for provider recommendation style, defined as indicated (provider stated vaccine was due at that visit) or not, and for child receipt of vaccines. Linear and logistic regression models were used to determine the relative contributions of parental intention and provider recommendation style to vaccine receipt. 56 parents/child dyads participated. 79% of children received HPV vaccines, and 93% received meningococcal vaccines. After controlling for demographic variables, parental intention did not differ by vaccine type. However, providers were less likely to use an indicated recommendation for HPV than for meningococcal vaccine. After controlling for demographic factors, parental intention, and provider recommendation style, vaccine type (HPV or meningococcal) was no longer associated with vaccine receipt Differences that were previously attributed to vaccine-specific factors may be explained by parents' and providers' roles in vaccine receipt. These findings suggest that interventions and policy recommendations regarding adolescent vaccination should focus on increasing parental demand for vaccines and ensuring that providers present all vaccines as the medical standard of care.